4-Aminothiophenol Strong SERS Signal Enhancement at Electrodeposited Silver Surface - Škantárová, Lenka; Oriňák, Andrej; Oriňáková, Renáta; Lofaj, František (Nano-Micro Letters, 2012)
Strong surface enhancement Raman spectroscopy signal of 4-aminothiophenol on silver substrate prepared by controlled electrodeposition is documented in this article. Enhancement factor was found to be affected not only by nanoparticle size, shape, orientation and spatial distribution, but also by interaction of Ag nanoparticles with thiol group of testing analyte. Self-assembled monolayers formation was contributed to this unique signal enhancement. The enhancement factor was established of 1.81×1014.